A series of climate oscillations around 8.2 ka revealed through multi-proxy speleothem records from North China - P. Duan; H. Li; Z. Ma; J. Zhao; X. Dong; A. Sinha; P. Hu; H. Zhang; Y. Ning; G. Zhu; H. Cheng (Climate of the Past, 2024)
The 8.2 ka event has been extensively investigated as a remarkable single event but rarely considered as a part of multi-centennial climatic evolution. Here, we present absolutely dated speleothem multi-proxy records spanning 9.0–7.9 ka from Beijing in North China, near the northern limit of the East Asian summer monsoon (EASM) and thus sensitive to climate change, to provide evidence of the intensified multi-decadal climatic oscillations since 8.52 ka. Three extreme excursions characterized by inter-decadal consecutive δ 18 O excursions exceeding ±1 σ are identified from 8.52 ka in our speleothem record. The earlier two are characterized by enriched 18 O at ∼8.50 and 8.20 ka, respectively, suggesting a prolonged arid event, which is supported by the positive trend in δ 13 C values, increased trace element ratios, and lower growth rate. Following the 8.2 ka event, an excessive rebound immediately emerges in our δ 18 O and trace element records but moderate in the δ 13 C, probably suggesting pluvial conditions and nonlinear response of the local ecosystem. Following two similar severe droughts at 8.50 and 8.20 ka, the different behavior of δ 13 C suggests the recovering degree of resilient ecosystem responding to different rebounded rainfall intensity. A comparison with other high-resolution records suggests that the two droughts–one pluvial pattern between 8.52 and 8.0 ka is of global significance instead of being a regional phenomenon, and is causally linked to the slowdown and acceleration of the Atlantic Meridional Overturning Circulation that was further dominated by the freshwater injections in the North Atlantic.